Avoiding unseen obstacles: Subcortical vision is not sufficient to maintain normal obstacle avoidance behaviour during reaching. (January 2018) - Ross, Alasdair I.; Schenk, Thomas; Billino, Jutta; Macleod, Mary J.; Hesse, Constanze
Abstract: Previous research found that a patient with cortical blindness (homonymous hemianopia) was able to successfully avoid an obstacle placed in his blind field, despite reporting no conscious awareness of it [Striemer, C. L., Chapman, C. S., & Goodale, M. A., 2009, PNAS, 106(37), 15996–16001]. This finding led to the suggestion that dorsal stream areas, that are assumed to mediate obstacle avoidance behaviour, may obtain their visual input primarily from subcortical pathways. Hence, it was suggested that normal obstacle avoidance behaviour can proceed without input from the primary visual cortex. Here we tried to replicate this finding in a group of patients ( N = 6) that suffered from highly circumscribed lesions in the occipital lobe (including V1) that spared the subcortical structures that have been associated with action-blindsight. We also tested if obstacle avoidance behaviour differs depending on whether obstacles are placed only in the blind field or in both the blind and intact visual field of the patients simultaneously. As expected, all patients successfully avoided obstacles placed in their intact visual field. However, none of them showed reliable avoidance behaviour – as indicated by adjustments in the hand trajectory in response to obstacle position – for obstacles placed in their blind visual field. The effects were not dependent on whether one or two obstacles were present. These findings suggest that behaviour in complex visuomotor tasks relies on visual input from occipital areas.